2014
DOI: 10.3233/npm-1471113
|View full text |Cite
|
Sign up to set email alerts
|

Fetal intestinal perforation and meconium peritonitis associated with maternal autoimmune hepatitis

Abstract: Autoimmune hepatitis (AIH) in pregnancy can affect both fetal and maternal outcomes. Little is known regarding the fetal outcomes of AIH in pregnancy. The major risks include spontaneous abortions, fetal mortality, perinatal mortality and prematurity. Two common drugs used in the management of AIH, azathioprine and prednisone, may also be associated with adverse fetal outcomes. We present the case of perinatal focal intestinal perforation with a meconium pseudocyst in a preterm infant of a mother with autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Seven studies addressed the disease activity change during pregnancy and mortality information, four addressed the comparison of pregnancy outcomes between different drug therapies, three population‐based cohort studies addressed the comparison of complications after delivery between AIH and matched non‐AIH populations. IPD from 26 case reports/series was extracted for systematic review 28–53 while no RCT was found. Five national cohort studies 25–27,54,55 were screened during literature searching and all of them were population‐based (AIH vs non‐AIH) among which, three were from Sweden 26,54,55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies addressed the disease activity change during pregnancy and mortality information, four addressed the comparison of pregnancy outcomes between different drug therapies, three population‐based cohort studies addressed the comparison of complications after delivery between AIH and matched non‐AIH populations. IPD from 26 case reports/series was extracted for systematic review 28–53 while no RCT was found. Five national cohort studies 25–27,54,55 were screened during literature searching and all of them were population‐based (AIH vs non‐AIH) among which, three were from Sweden 26,54,55 .…”
Section: Resultsmentioning
confidence: 99%
“…For the systematic review, a total of 16 case reports, 10 case series (sample sizes ranging from 2 to 7) published between 1960 and 2018 were screened 28–53 . IPD from each study was collected using a pre‐designed form.…”
Section: Resultsmentioning
confidence: 99%
“…The co-occurrence of MP and ICP has not been reported in previous studies, but there are six reported cases of fetal MP associated with maternal hepatic diseases in the literature. [24][25][26][27][28] In view of a possible association between maternal ICP and fetal MP, perhaps, serial ultrasound surveillance in pregnancies with ICP should be considered for early detection of fetal MP, and vice versa; perhaps, maternal serum total bile acid level should be monitored in patients with MP.…”
Section: Polyhydramnios Is Likelymentioning
confidence: 99%